Surgical fear questionnaire (SFQ) – Serbian cultural adaptation - Janković, Slobodan M; Antonijević, Gordana V; Mirković, Snježana N; Raspopović, Katarina M; Radoičić, Ljiljana R; Putnik, Srdjan S; Živković-Radojević, Marija N; Vasić, Ivana R; Nikolić, Boško V; Stanojević, Dragan R; Teofilov, Sladjana D; Tomašević, Katarina V; et al. (Vojnosanitetski pregled, 2021)
Background/Aim. After having established an indication for surgery, some patients experience sense of fear, unpleasantness and embarrassment due to the expectance of adverse consequences of surgical intervention. Recently an instrument for measuring fear of surgery – the Surgical Fear Questionnaire (SFQ) – was developed and validated on a sample of Dutch patients awaiting surgery. The objective of this study was to translate the SFQ to Serbian language, make cultural adaptation of the translation and test its reliability and validity in a sample of outpatients in Serbia. Methods. The SFQ was translated and adapted according to the accepted international standards (double forward translation, harmonization, backward translation, and piloting). The study was multicentric, involving patients from 7 cities in 3 countries: Serbia, Montenegro, Bosnia and Hercegovina. It was conducted at state-owned health facilities. The sample was of consecutive nature and consisted of 330 outpatients who visited specialists of either internal medicine or general surgery. Results. Translated SFQ showed excellent reliability, both when rated by the investigators (Cronbach’s alpha 0.915), and by the patients themselves (Cronbach’s alpha 0.917). It is temporally stable, and both divergent and convergent validity tests had good results. Factorial analysis revealed one domain on the whole study sample and two domains like in original on the subsample of patients without experience with surgery in general anesthesia. Conclusion. Identification of patients with high level of fear of surgery by this questionnaire should help clinicians to administer measures which may decrease fear and prevent avoidance of absolutely necessary surgery by such patients.
Keywords: fear; surgical procedures, operative; surveys and questionnaires; serbia; language